From Slavery to Fair Work in Hospitality: How New Technologies Affect? - Elmohandes, Nirmeen; Marghany, Mostafa (Economica, 2025)
This critical review examines the role of advanced technologies in reshaping slavery-like working conditions in the hospitality industry. While automation and intelligent systems can improve efficiency and ease workloads, they also raise concerns about worker displacement, wage disparities, and job insecurity. The discussion revolves around whether technological advancements can improve working conditions or deepen existing inequalities by favouring highly skilled workers while marginalising others. The existing literature does not provide a unified framework that guarantees ethical employment practices by combining technology with labour force policies. The study introduces the Tech-Driven Fair and Decent Work Agenda (TDFDWA) as an approach towards implementing the Fair and Decent Work Agenda (FDWA), sustainable development goals (SDG 8) and International Labour Organization (ILO), aiming to integrate advanced technologies in implementing ethical labour governance. This agenda harnesses advanced technologies for promoting economic growth and ethical employment to ensure labour force stability in the age of the digitalised hospitality industry.